Hazardous Geology and Environmental Geology - Kastwar, Parul; Vishwakarma, Chaitali (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
Environmental geology and hazard geology are critical fields that intersect the natural processes of the Earth with human activities, focusing on understanding and mitigating the impacts of geological hazards. This review explores the key concepts, recent advancements, and future directions in these disciplines, emphasizing the importance of interdisciplinary approaches in addressing complex environmental and hazard-related challenges. Key areas such as soil and water contamination, land-use planning, and resource management are discussed within the context of environmental geology, while hazard geology is examined through the lens of earthquakes, landslides, floods, and volcanic eruptions. Recent technological innovations, including remote sensing, geophysical techniques, and early warning systems, are highlighted for their role in enhancing hazard prediction and mitigation. Additionally, the review underscores the significance of integrating geological insights into sustainable development practices, policy frameworks, and public education to build resilient communities capable of withstanding geological threats.